7(6m-6)+3=-81

Simple and best practice solution for 7(6m-6)+3=-81 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(6m-6)+3=-81 equation:


Simplifying
7(6m + -6) + 3 = -81

Reorder the terms:
7(-6 + 6m) + 3 = -81
(-6 * 7 + 6m * 7) + 3 = -81
(-42 + 42m) + 3 = -81

Reorder the terms:
-42 + 3 + 42m = -81

Combine like terms: -42 + 3 = -39
-39 + 42m = -81

Solving
-39 + 42m = -81

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '39' to each side of the equation.
-39 + 39 + 42m = -81 + 39

Combine like terms: -39 + 39 = 0
0 + 42m = -81 + 39
42m = -81 + 39

Combine like terms: -81 + 39 = -42
42m = -42

Divide each side by '42'.
m = -1

Simplifying
m = -1

See similar equations:

| 8t-16= | | 2x+8=14x+12 | | y=t+t-y | | 3(-40+-2r)+20= | | y-2=.10(x+10) | | 2•-4/5 | | 6-4(2x+8)=16 | | (t-3)7=6+21 | | 6x-13=90 | | 8[t-2]= | | 4v+4=4 | | 4p+1=-15 | | 4k-3(k-8)=2(3-5k)+7 | | 50-5x=80-17x | | 15y-(3-[4y+4]+57)=2-y | | 2(6-4x)=21-9x | | -7+(8z+2)=(7z+5)+1 | | 3.7+15.09= | | -1/3m=-8 | | r^2-8=26 | | Z-2=4+9x | | 4.5[h-6]= | | 19x+3=11x-2 | | 5/8j-3/4=1/2 | | .5d-3/4=3/5d | | 79-2x=88-3x | | 3y-7=4y+8 | | -1/2(6x-1/3) | | 5p^2=230 | | 9x-8=x+10 | | 5x^2+4x-48=0 | | -2=-3/5x-3 |

Equations solver categories